What encourages households to adopt rice as a new crop? Understanding gender roles and perceptions in households in northern Namibia. Issue 7 (3rd October 2017) - Kaida, Kiyomi; Nishikawa, Yoshiaki; Benisiu, Thomas; Shivolo, Ottilie; Hango, Vistorina
ABSTRACT: This article investigates how the introduction of new crops influences intra-household decision-making among the Ovambo in northern Namibia where women are responsible for crop farming, while men are engaged in livestock farming. It examines gender relations that underlie daily activities. The findings of the study show that women try new crops on their own or with the help of their children and do not negotiate with their husband, mothers, or brothers over household resources such as land, labour, and the cash of other family members. Women avoid conflicts with family members, but may have an increased perception of contribution to the household if they succeed in introducing new crops.